The Effect of the Implementation of Mandatory Zakat Law on Tax Revenue in Indonesia - Mani, Dwi Mutiara Kintan; Isman, Isman; Budiman, Mamdukh (Universitas Muhammadiyah Surakarta, 2025)
This study analyzes the impact of the implementation of mandatory zakat laws on tax revenue in Indonesia in the period 2023–2024 using a legal analysis approach. The focus of this study is on the relationship and overlap between zakat and tax obligations in the context of state fiscal policy. The method used is quantitative research with a normative approach, where data is collected through literature studies and analyzed using legal content analysis techniques. The results of the study show that although the implementation of the mandatory zakat law through the role of the National Zakat Agency (BAZNAS) has the potential to increase public compliance with financial obligations, data for the 2023–2024 period shows fluctuations in tax revenue, indicating that there has not been an optimal substitution between zakat and taxes. This is due to the lack of regulations that fully integrate zakat as a tax deduction and the lack of socialization to taxpayers. This study concludes that to optimize the integration of zakat and taxes, regulatory harmonization and clearer and more effective fiscal incentive policies are needed.